2021
DOI: 10.1111/are.15236
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gene expression associated with LC‐PUFA metabolism in juvenile tambaqui ( Colossoma macropomum ) fed different dietary oil sources

Abstract: Given the ecological unsustainability of using fish oil (FO) as the main source of longchain polyunsaturated fatty acids (LC-PUFA), the investigation of alternative dietary LC-PUFA sources is crucial for aquaculture. Tambaqui (Colossoma macropomum) is a valuable economic aquaculture resource in Brazil, capable of endogenously elongating and desaturating linoleic (LA; 18:2n-6) and α-linolenic (ALA; 18:3n-3) acids to longer and physiologically vital LC-PUFA. Yet, it is unclear how this pathway is regulated by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…An in vivo study of tambaqui (Colossoma macropomum) also showed that a high expression level of fads2 and elovl2 was found in the brain of fish fed VO diets compared with those of fish fed FO diets. 37 Actually, the LC-PUFA biosynthetic capacity of the brain does not only depend on the exogenous dietary fatty acids but also depends on the endogenous LC-PUFA from the liver. 38 Maintaining high LC-PUFA levels is essential for the structure, function, and neurotransmission of the brain; therefore, the fatty acid compositions of critical neural tissues are less representative of dietary-provided fatty acids.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vivo study of tambaqui (Colossoma macropomum) also showed that a high expression level of fads2 and elovl2 was found in the brain of fish fed VO diets compared with those of fish fed FO diets. 37 Actually, the LC-PUFA biosynthetic capacity of the brain does not only depend on the exogenous dietary fatty acids but also depends on the endogenous LC-PUFA from the liver. 38 Maintaining high LC-PUFA levels is essential for the structure, function, and neurotransmission of the brain; therefore, the fatty acid compositions of critical neural tissues are less representative of dietary-provided fatty acids.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These findings supported the suggestion that the brain is an organ for the rapid accumulation of DHA but not for effective biosynthesis of DHA. , However, numerous studies reported that an apparent expression of fads2 and elovl genes was observed in the brain of teleosts, and it seems, to some extent, that the brain possesses the high capacity of LC-PUFA biosynthesis. An in vivo study of tambaqui (Colossoma macropomum) also showed that a high expression level of fads2 and elovl2 was found in the brain of fish fed VO diets compared with those of fish fed FO diets . Actually, the LC-PUFA biosynthetic capacity of the brain does not only depend on the exogenous dietary fatty acids but also depends on the endogenous LC-PUFA from the liver .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Leaver et al [ 24 ] identified four different genes for the PPARδ subtype in Atlantic salmon ( Salmo salar ), of which at least two were shown to be functional, consistent with a fourth round of whole-genome duplication (4R WGD) inferred to the Salmoniformes lineage [ 31 ]. Subsequently, through gene/cDNA cloning, or through genomic analyses, two distinct isoforms of PPARα were identified in the turbot ( Scopthalmus maximus ) [ 32 , 33 ], the loach ( Misgurnus anguillicaudatus ) [ 34 ], the Japanese sea bass ( Lateolabrax japonicus ) [ 35 ], the brown trout (Salmo trutta ) [ 36 ], the tambaqui ( Colossoma macropomum ) [ 37 ], and the cod ( Gadus morhua ) [ 38 ]. Similarly, two PPARδ isotypes were identified in the tambaqui [ 37 ] and the loach [ 39 ].…”
Section: Ppar Isotypes and Isoforms In Fish Species: Diversity Reflec...mentioning
confidence: 99%
“…Subsequently, through gene/cDNA cloning, or through genomic analyses, two distinct isoforms of PPARα were identified in the turbot ( Scopthalmus maximus ) [ 32 , 33 ], the loach ( Misgurnus anguillicaudatus ) [ 34 ], the Japanese sea bass ( Lateolabrax japonicus ) [ 35 ], the brown trout (Salmo trutta ) [ 36 ], the tambaqui ( Colossoma macropomum ) [ 37 ], and the cod ( Gadus morhua ) [ 38 ]. Similarly, two PPARδ isotypes were identified in the tambaqui [ 37 ] and the loach [ 39 ]. The duplication of the PPARγ gene in a teleost fish was first established in the blind cave fish ( Astyanax mexicanus ) [ 26 ], while more recently through comparative genomic and phylogenetic analyses, [ 40 ] two PPARγ genes were identified in the genomes of European sardine, Sardina pilchardus (Clupeiformes), herring, Clupea harengus (Clupeiformes), red-bellied piranha, Pygocentrus nattereri (Characiformes), northern pike, Esox lucius (Esociformes), and channel catfish Ictalurus punctatus (Siluriformes), as well as in the salmonid species Atlantic salmon, Coho salmon ( Oncorynchus kisutch ), and rainbow trout ( Oncorynchus mykiss ).…”
Section: Ppar Isotypes and Isoforms In Fish Species: Diversity Reflec...mentioning
confidence: 99%
See 1 more Smart Citation